cAMP Receptor Protein Controls Vibrio cholerae Gene Expression in Response to Host Colonization - Jainaba Manneh-Roussel (American Society for Microbiology, 2018)
ABSTRACT The bacterium Vibrio cholerae is native to aquatic environments and can switch lifestyles to cause disease in humans. Lifestyle switching requires modulation of genetic systems for quorum sensing, intestinal colonization, and toxin production. Much of this regulation occurs at the level of gene expression and is controlled by transcription factors. In this work, we have mapped the binding of cAMP receptor protein (CRP) and RNA polymerase across the V. cholerae genome. We show that CRP is an integral component of the regulatory network that controls lifestyle switching. Focusing on a locus necessary for toxin transport, we demonstrate CRP-dependent regulation of gene expression in response to host colonization. Examination of further CRP-targeted genes reveals that this behavior is commonplace. Hence, CRP is a key regulator of many V. cholerae genes in response to lifestyle changes. IMPORTANCE Cholera is an infectious disease that is caused by the bacterium Vibrio cholerae. Best known for causing disease in humans, the bacterium is most commonly found in aquatic ecosystems. Hence, humans acquire cholera following ingestion of food or water contaminated with V. cholerae. Transition between an aquatic environment and a human host triggers a lifestyle switch that involves reprogramming of V. cholerae gene expression patterns. This process is controlled by a network of transcription factors. In this paper, we show that the cAMP receptor protein (CRP) is a key regulator of V. cholerae gene expression in response to lifestyle changes.